Canonical mRNA is the exception, rather than the rule - Jun-An Chen; Simon Conn (Genome Biology, 2017)
Abstract A report on the Second Aegean International Conference on the Long and the Short of Non-Coding RNAs, held in Heraklion, Greece, 9–14 June 2017.